2023
DOI: 10.21203/rs.3.rs-3318458/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consequences of drought regimes on the water footprint of agricultural production. Temporal analysis of the Guadalupe Valley, Mexico.

Vanessa Novoa,
Carolina Rojas,
Octavio Rojas
et al.

Abstract: Changes in water availability have a strong impact on the sustainability and maintenance of agriculture, with water footprint (WF) being a robust methodology to assess these transformations. The Guadalupe Valley is one of the places with the highest agricultural production in Mexico. Despite its semi-arid climatic conditions, it provides high-quality crops that are well-positioned in the world. The historical trend of rainfall and temperatures between 1987-2017 was analyzed with the purpose of identifying clim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The analysis of avocado cultivation in the municipalities of Acuitzio and Morelia revealed how the increase in rainfall has a significant impact on the results of the water footprint, a situation similar to that reported by Novoa et al [58] in the Valle de Guadalupe, Mexico, where it was shown that in the driest years there is a greater consumption of water in the vine and olive crops and lower consumption in years with higher humidity. Another study is that of Reyes and Naranjo [59] in Quindío, Colombia, which demonstrated that the precipitation contribution is enough to cope with the water needs of the avocado crop at that study site.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The analysis of avocado cultivation in the municipalities of Acuitzio and Morelia revealed how the increase in rainfall has a significant impact on the results of the water footprint, a situation similar to that reported by Novoa et al [58] in the Valle de Guadalupe, Mexico, where it was shown that in the driest years there is a greater consumption of water in the vine and olive crops and lower consumption in years with higher humidity. Another study is that of Reyes and Naranjo [59] in Quindío, Colombia, which demonstrated that the precipitation contribution is enough to cope with the water needs of the avocado crop at that study site.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the water stress of irrigation water use, Jiang et al [11] report that dependence on blue water in the Tarim River Basin in China has caused imbalances in water use; another similar study is that of Novoa et al [58] where, in the words of the author, they detected unsustainability in the upper basin of the Cachapoal River in Chile, based on the blue water footprint indicator and caused mainly by climatic variations. In the case of Wedaa et al [65], research shows how irrigated agricultural crops in Iraq have had to switch to seasonal crops due to the scarcity of blue water.…”
Section: Discussionmentioning
confidence: 89%